2018
DOI: 10.1111/jocs.13775
|View full text |Cite
|
Sign up to set email alerts
|

Early and midterm outcomes of transcatheter aortic valve replacement in patients with bicuspid aortic valves

Abstract: TAVR in BAV disease is feasible with favorable valve performance. Immediate and mid-term outcomes of TAVR in patients with BAV are comparable to those with TAV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…With the recent improvements in pre-procedural imaging and devices, transcatheter aortic valve implantation (TAVI) is considered a safe and feasible treatment option for aortic valve stenosis with BAV 12 . Furthermore, it has been reported that TAVI could be performed safely in patients with a mildly dilated ascending aorta and low intraprocedural risk 13 .…”
Section: Introductionmentioning
confidence: 99%
“…With the recent improvements in pre-procedural imaging and devices, transcatheter aortic valve implantation (TAVI) is considered a safe and feasible treatment option for aortic valve stenosis with BAV 12 . Furthermore, it has been reported that TAVI could be performed safely in patients with a mildly dilated ascending aorta and low intraprocedural risk 13 .…”
Section: Introductionmentioning
confidence: 99%
“…A total of 14924 patients(BAV: 4986 patients; TAV: 9938 patients) in 20 studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] were eligibility for the current meta analysis. According to the Newcastle-Ottawa Scale(0-9), 18 studies represented high quality(a score of[?]…”
Section: Resultsmentioning
confidence: 99%
“…19 studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][27][28][29][30] reported post-procedural MAG, and 7 studies 11,[14][15][16][17]25,27 reported post-procedural AVA. The data of MAG in the 15 studies 11,[13][14][15][16][17]20,[22][23][24][25][27][28][29][30] and AVA in all the 7 studies were expressed as the mean±SD(n), and were taken into comparison independently. 4 studies 12,18,19,21 were excluded because the data were expressed as median and interquatile range.…”
Section: Comparison Of Efficacy Endpointsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely due to the more difficult technical aspects of treating this population, as a bicuspid aortic valve is associated with an elliptical or asymmetric annulus and enlarged ascending aorta [38][39][40]. However, this anomaly is the most prevalent congenital heart disease, involving 1% of the population, and is the etiology of roughly 20% of patients over 80 years old with aortic stenosis [38][39][40]. With this significant population of aortic stenosis patients, TAVR has been provided as an off-label solution to treat this disease, with multiple smaller studies published.…”
Section: Emerging Evidencementioning
confidence: 99%